DERIVING THE EQUATION OF STATE FOR LIQUIDS AND EXTENSION OF THE PRINCIPLE OF CORRESPONDING STATES (Journal of Sciences, Islamic Republic of Iran)
A new simple model is introduced for a liquid and an equation of state is derived based on this model and the statistical mechanical calculations. This equation of state works well for the non-polar and slightly polar liquids. The important conclusion that may be deduced from this equation of state is that if the reduced variables of state are chosen and defined appropriately, then, the principle of corresponding states works well for liquids, and it may even be unnecessary to use an additional parameter like the acentric factor